The Use of Digital Comick Media in Improving the Reading Ability of Grade V Students of State Elementary School - Rehiara, Indry Lenisari; Ririhena, Ribka L.; Notanubun, Zainudin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This research is motivated by students' low reading ability and interest in understanding the contents of the text, which is reflected in learning outcomes that have not reached the minimum completion criteria. This study aims to strengthen the reading comprehension skills of fifth-grade elementary school students by utilizing digital comic media, which integrates text and images in an intriguing and meaningful way. This Classroom Action Research (CAR) was carried out in two cycles, where each cycle consists of the stages of planning, implementation, observation, and reflection. The research subjects were 23 fifth-grade students at State Elementary School 1 Poka in the even semester of the 2024/2025 academic year. Data were collected through observation, tests, and documentation, then analyzed qualitatively and quantitatively. The results indicated a substantial improvement in students' reading comprehension skills in every cycle. The average pre-test score was 48.68 with a completion percentage of only 13%. After the implementation of cycle I, the average increased to 63.03 (43% completion) and reached 76.51 with 100% classical completion in cycle II. This improvement occurred in all aspects of comprehension, including character identification, story content comprehension, and message interpretation. As a major contribution, this study demonstrates that the use of digital comics has proven effective in improving students' reading comprehension learning outcomes, as well as fostering students' interest in reading and active participation in the learning process. Digital comics are suggested as a novel approach to mitigate the issue of inadequate reading comprehension skills in elementary education.